Identification of Drought Tolerant and Molecular Analysis of DREB2A and BADH2 Genes and Yield Potensial of Lines from Single Crossing Bengkulu Local Rice Varieties - Reny Herawati; ALNOPRI ALNOPRI; MASDAR MASDAR; MARULAK SIMARMATA; SIPRIYADI SIPRIYADI; MIMI SUTRAWATI (Biodiversitas Journal of Biological Diversity, 2021)
Screening in the seedling stage of 39 progeny of F6 lines to drought stress was carried out in the greenhouse.  Drought tolerant and sensitive varieties of IR 20 and Salumpikit, respectively, were used as control plants.  The methods for traits identification of leaf curled, dried, and recovery ability after exposure to severe drought for two weeks was following the Standard Evaluation System (SES) developed by IRRI.  Molecular analysis to detect the presence of the DREB2A gene was carried out by PCR amplification of genomic DNA using forward- and reverse- oligonucleotide primers of CCTCATTGGGTCAGGAAGAA and GGATCTCAGCCACCCACTTA, respectively, while for BADH2 gene using forward- and reverse- oligonucleotide primers of GGCCAAGTACCTCAAGGCGA and TGTCCCCAGCTGCTTCATCC, respectively.  Molecular markers of DREB2A and BADH2 genes were also identified in 39 tested lines with approximately 250 and 2300 bp length, respectively.  This study concluded that the progeny of F6 lines generating from the crossing of local varieties of IR7858 and IR148 is the potential to become a drought-tolerant variety of upland rice. Line numbers BKL2 B-2-264-6 and BKL4 B-1-268-10 have a potential yield of more than 12 tonnes/ha. These line has the potential to be developed on rainfed lowland rice or dry land because it has drought resistance.